2022
DOI: 10.1016/j.jcot.2022.101775
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of orthopaedic related publications by Indian authors from the last decade

Abstract: Bibliometric studies have been established methods of analysing publications on a particular topic. These studies have been done on various orthopaedic topics and are increasing. The advantages of these studies have been highlighted in previous publications. Although some studies have been done on Indian publications from other specialties, those analysing Indian Orthopaedic Publications are lacking. Methods: We performed a search in Scopus to look for all publications related to orthopaedics from India. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Vaishya et al reported that India's publications in orthopaedics grew at a rate of 20.8% annually in the last two decades, and 10.4% of Indian studies received external funding and 16.3% were international collaborations. 30 Karlapudi et al 31 found New Delhi to be the epicenter of publications related to orthopaedics, similar to our findings related to fractures. Vaish et al 32 found that in Indian HCPs related to orthopaedics 24.58% publications received external funding and 36.87% publications were an international collaboration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Vaishya et al reported that India's publications in orthopaedics grew at a rate of 20.8% annually in the last two decades, and 10.4% of Indian studies received external funding and 16.3% were international collaborations. 30 Karlapudi et al 31 found New Delhi to be the epicenter of publications related to orthopaedics, similar to our findings related to fractures. Vaish et al 32 found that in Indian HCPs related to orthopaedics 24.58% publications received external funding and 36.87% publications were an international collaboration.…”
Section: Discussionsupporting
confidence: 91%
“…Despite a large burden of fractures in the Indian population, due to road accidents 1 2 and other causes, not much research has been done so far, especially on the prevalence of these fractures and the published literature from Indian authors on this topic. However, the research output of the Indian authors in other fields like orthopaedics 30 31 32 and arthroplasty 33 have been studied. Rupp et al 34 found an increase in the incidence of fractures by 14% in Germany between 2009 and 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of HCP (126/128) were original research (n=89) and review (n=37). Karlapudi et al (2022) studied the Orthopaedic related publications by Indian authors and observed that the basic science related papers were more cited than the 'general category' articles. Similar to our study, Lao et al (2013) reported a significant annual increase in Orthopaedic publications between 2000 to 2012 from the USA, Japan and China, with the USA contributing maximally at 35.3% of the total world output in orthopedics in 2012, and accumulated the highest number of citations.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In recent years, there has been increased transparency in the disclosure of publication data in the field of orthopedics in some countries. 1 , 2 , 6 , 18 , 19 However, little is known about how Canada ranks in terms of orthopedic research productivity on a global scale or about the contribution of orthopedic research to the overall scientific research output of the country. The purpose of this study was to determine the contribution of Canadian authors to the orthopedic literature both nationally and globally, productivity in orthopedic research in Canada, the productivity in orthopedics of individual academic centres and the level of networking and collaboration in Canadian centres.…”
mentioning
confidence: 99%
“…A number of factors have been described to assess academic productivity using this model, in terms of both the volume and the scientific impact of the research produced. Bibliometric analysis allows for a broad and complete evaluation of the productivity and scientific impact of the research produced in a particular country or specific discipline (such as medicine or surgery), [1][2][3][4][5] individual journals [6][7][8] and studies presented at annual scientific meetings, [9][10][11] as well as the impact of individual authors. 3,12,13 Using this model, Saab and colleagues showed that orthopedic research originating in France has increased by more than 50% over the past 10 years.…”
mentioning
confidence: 99%